CHILDCARE AND CHALLENGES RESULTING FROM THE COVID-19 PANDEMIC: Childcare and challenges resulting from the COVID-19 pandemic - Smaniotto Madeira, Maria Eduarda; Wisniewski Setter, Nathalia; Laschewitz Wamser, Johanna; Marcon, Leticia; Maysa de Souza, Daniela (Saúde em Redes, 2023)
To analyze, from a medical perspective, the avoidance of childcare consultations during the COVID-19 pandemic. This is a qualitative and descriptive research, which was carried out with five physicians working in Family Health Strategies located in the city of xxx, in the Médio Vale do Itajaí, in Santa Catarina. The data was collected in July and August 2022, through interviews (recorded and transcripted), using a semi-structured questionnaire, through the snowball method, choosing thematic analysis to analyze the data. The research was approved under number CAAE xxx. The COVID-19 pandemic had a negative impact on the follow-up of childcare consultations and the main repercussions are related to the reduction in consultations; delay in monitoring neuropsychomotor development; increase in respiratory cases with the return of children to daycare centers and low rates of vaccination coverage. In addition, nutritional aspects were highlighted, such as early weaning and changes in eating habits (with weight gain or loss). So far, the implication sof COVID-19 in childcare have become invaluable, therefore, the study data bring relevant information for planning strategies to strengthen childcare actions, health promotion and disease prevention.